Gibbon, Maureen (London, 2013)
2013 "Gibbon, Maureen", 2013, HistoryTalk Maureen was born in Ilford, the eldest of three children, after her parents had moved back to London after the war. She worked in various part time jobs in Ilford and Rainham as a teenager, including in a library, at Jeyes Fluids and as a waitress. Although she did A levels at school, she did not go to university but did a secretarial course. Her first job was working for a research company in Soho in the early days of market research around 1962 and was earning about £6 per week. In 1963, she moved to work as a supply teacher at the Rosetta Infants and Primary School in Canning Town. She describes in detail some of the children at the school and her enjoyment of teaching there. She then went into factory work in 1964 until her daughter Jo was born. She then did cleaning jobs in Notting Hill and recalls playgroups in north Kensington around St Marks Road and the Spanish and Portuguese communities in that area.